LABVIEW BASED USER INTERFACE FOR ENERGY FORECAST SOFTWARE WITH ANDROID INTERFACING - Mohamed Zaini, Muhammad Aizat (Universiti Teknologi Petronas, 2013)
Interfacing of LabVIEW with the outside world by using external data acquisition hardware has seen many different applications being developed from a simple data acquisition to instrument control. However, development of interfacing LabVIEW program with an Android mobile application has yet to be published in recent years although there is a LabVIEW application developed for Android platform itself which is small scale version of the software used to quickly view the front panel and block diagram of LabVIEW programs. This paper will stress on the development of LabVIEW virtual instrument (VI) alongside with an Android mobile application that can be used to input arrays of data into it and send the data through Bluetooth communication medium for further processing within LabVIEW. The communication will be of 2-way communication where the Android application can send and receive data to and from LabVIEW. In order to complete the build environment of this project, a test model will be used and programmed into LabVIEW specifically a time-series load forecasting model. This model will require the final user to input an array of load data from Android, and send them to LabVIEW for processing with the load forecasting model. Results generated from LabVIEW will be sent to Android for viewing and analysis.